Multiple effects of magnesium isoglycyrrhizinate on the disposition of docetaxel in docetaxel-induced liver injury. (3rd April 2017) - Qu, Biao; Xing, Rong; Wang, Hong; Chen, Xin; Ge, Qin; Peng, Daiyin; Wang, Guangji
Abstract: 1. Magnesium isoglycyrrhizinate (MgIg) has been extensively used in treating liver injury which is the common adverse reaction of docetaxel (DOC). Due to the narrow therapeutic window, small changes in pharmacokinetic profiles can alter the toxicity and therapeutic efficacy of DOC significantly. The study aimed to explore the effects of MgIg on the disposition of DOC and the potential mechanism in DOC-induced liver injury. 2. Pharmacokinetics and tissues distribution behaviors showed that there was no significant difference between DOC group (DOCG) and MgIg + DOC group (MDOCG). The mRNA and protein levels of cytochrome P450 3A1 (CYP3A1) in liver, intestine, and kidney were significantly upregulated, and the P-glycoprotein (P-gp) was obviously downregulated in MDOCG when compared with DOCG. 3. Immunoglobulin M (IgM), CD8 + were upregulated in DOCG; while in MDOCG, IgM, CD8 + recovered to normal levels and complement C3 ; CD4 +  were upregulated. 4. MgIg had no significant effects on the disposition of DOC in docetaxel-induced liver injury. Additional, potential drug–drug interaction may happen if MgIg co-administered with antitumor drugs which are the substrates of CYP3A4 or P-gp. Hepatoprotective mechanism of MgIg perhaps was through upregulation of C3, CD4 + and downregulation of IgM, CD8 + .